2010
DOI: 10.1007/s10722-010-9641-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological status of Allium hookeri Thwaites (2n = 22)

Abstract: Determining the base number, ploidy level and type of ploidy are important aspects in the cytogenetic study of a species. To assess the nature of Allium hookeri Thwaites (2n=22), chromosomes of its two populations from North-eastern Himalayas were worked out for morphological details, putative grouping and pairing properties during reduction division. Karyotype was found to split into 7 pairs and 8 single chromosomes; 7 pairs revealed minor differences in overall chromosome morphology. Critical analysis of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…On the other hand L. cylindrica shows much higher frequency of abnormalities in pollen mother cells. These Meiotic irregularities leading to dip in pollen viability is expected and is reported in several angiosperm taxa [10,[18][19][20][21]. The disadvantage in the meiotic system not withstanding L. cylindrica is reproductively much efficient as compared to L. acutangula.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand L. cylindrica shows much higher frequency of abnormalities in pollen mother cells. These Meiotic irregularities leading to dip in pollen viability is expected and is reported in several angiosperm taxa [10,[18][19][20][21]. The disadvantage in the meiotic system not withstanding L. cylindrica is reproductively much efficient as compared to L. acutangula.…”
Section: Discussionmentioning
confidence: 52%
“…4d). Sharma et al (2011) documented that A. hookeri is a segmental allotriploid since its karyotype can be split into 7 pairs with minor differences and 8 single chromosomes. Taking the paraphyletic relationships among the species with x = 11 into consideration (Huang 2014), we advocate that all species within sect.…”
Section: Discussionmentioning
confidence: 99%
“…Allium hookeri (AH) belongs to a member of the Alliaceae family and is found in India, Greece, Sri Lanka, Myanmar (Burma), southern western China (Tibet, Yunnan, and Shchuan), Bhutan, and South Korea. It has been used by locals to treat coughs, colds, wounds, and burn (Sharma, Gohil, & Kaul, ). Our previous study reported that AH alleviated clinical symptoms of allergic rhinitis in an animal model (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%